Erratum - Office, Editorial (Archives of Mechanics, 2012)
Erratum to: G. Dzierżanowski, T. Lewiński, Compliance minimization of thin plates made of material with predefined Kelvin moduli. Part I. Solving the local optimization problem, Arch. Mech., 64, 1, 21–40, 2012 (in printed version only).